Melanonychias - Di Chiacchio, Nilton; Tosti, Antonella (Springer International Publishing : Imprint: Springer, 2017)
The purpose of this book is to guide the dermatologist and the general physician in the differential diagnosis and treatment of melanonychias. Melanonychia is a longitudinal pigmentation of the nail and it is considering a common presenting problem in general dermatology. The differential diagnosis varies from subungual hematoma to a fungal infection to a melanocytic lesion (hypermelanosis, lentigo, nevus, and melanoma) among others. Melanonychia may also indicate an early stage of nail melanoma, and its diagnosis remains a challenge among dermatologist. A recent publication on Dermatologists accuracy in early diagnosis of melanoma of the nail matrix showed that in situ melanoma of the nail matrix is very difficult for dermatologists to diagnose, regardless of the level of their experience. On Melanonychias the reader will find a complete discussion about all the most important topics on this condition, since its basic aspects (such as nail anatomy and epidemiology) until applied topics (including clinical features, nail biopsy and treatment).
Keywords: Medicine.; Dermatology.; elektronické knihy; electronic books